Yeast Bax inhibitor, Bxi1p, is an ER-localized protein that links the unfolded protein response and programmed cell death in Saccharomyces cerevisiae. - James Cebulski; Joshua Malouin; Nathan Pinches; Vincent Cascio; Nicanor Austriaco (PLoS ONE)
Bax inhibitor-1 (BI-1) is an anti-apoptotic gene whose expression is upregulated in a wide range of human cancers. Studies in both mammalian and plant cells suggest that the BI-1 protein resides in the endoplasmic reticulum and is involved in the unfolded protein response (UPR) that is triggered by ER stress. It is thought to act via a mechanism involving altered calcium dynamics. In this paper, we provide evidence that the Saccharomyces cerevisiae protein encoded by the open reading frame, YNL305C, is a bona fide homolog for BI-1. First, we confirm that yeast cells from two different strain backgrounds lacking YNL305C, which we have renamed BXI1, are more sensitive to heat-shock induced cell death than wildtype controls even though they have indistinguishable growth rates at 30°C. They are also more susceptible both to ethanol-induced and to glucose-induced programmed cell death. Significantly, we show that Bxi1p-GFP colocalizes with the ER localized protein Sec63p-RFP. We have also discovered that Δbxi1 cells are not only more sensitive to drugs that induce ER stress, but also have a decreased unfolded protein response as measured with a UPRE-lacZ reporter. Finally, we have discovered that deleting BXI1 diminishes the calcium signaling response in response to the accumulation of unfolded proteins in the ER as measured by a calcineurin-dependent CDRE-lacZ reporter. In toto, our data suggests that the Bxi1p, like its metazoan homologs, is an ER-localized protein that links the unfolded protein response and programmed cell death.